The Importance of Pediatric Scoring Systems of Multiorgan Failure in Intensive Care Unit (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: pediatric scoring systems; multiple organ dysfunction syndrome-MODS; intensive care unit